The role of physical recreation in the life of Russian combat veterans returning after a special military operation - Evgrafov I.E. (Theory and Practice of Physical Culture, 2025)
The relevance of physical recreation in the lives of combat veterans is highlighted, as it plays a crucial role in their physical and psychological recovery and aids in their successful reintegration into society. This study aims to explore the key elements of physical recreation that facilitate the restoration of physical fitness and psychological stability in veterans returning from special military operations. The findings indicate that physical activity is essential for restoring fitness levels—enhancing strength, endurance, flexibility, and coordination—especially for veterans with injuries and disabilities. Engaging in sports is found to alleviate stress, anxiety, and depression, while the production of endorphins during exercise contributes to improved mood and emotional stability. Additionally, group activities foster socialization and help combat feelings of isolation. Regular exercise is effective in mitigating chronic pain and normalizing sleep patterns in veterans suffering from insomnia or other sleep disorders. Participation in sports events and group training also enhances social integration, enabling veterans to build friendships and a sense of community. It is emphasized that the choice of physical activities should consider individual characteristics, physical conditions, and personal preferences, with recommendations to consult healthcare professionals and adaptive physical education specialists. Various forms of exercise, including adapted physical education, cardiovascular training, strength training, yoga, and outdoor activities, are suggested to optimize rehabilitation efforts. A sociological survey conducted among cadets at the Kazan Higher Tank Command School revealed that 50% spend their free time with family in nature, while 20% engage in physical activities for recovery. The study concludes that physical recreation can be a vital component in the rehabilitation and reintegration of war veterans, supporting their transition to a fulfilling life.